Integrating Artificial Intelligence in HR Decision Making: Impacts on Organizational Efficiency and Fairness - Afriani Pravitasari; Nurul Aisyah; Rani Suryani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
This study explores the impact of Artificial Intelligence (AI) integration and algorithm transparency on organizational efficiency and perceived fairness in Human Resource (HR) decision-making. Using a qualitative literature review approach, the research examines the mediating role of employee trust and the moderating influence of organizational culture. The analysis focuses on peer-reviewed international studies published since 2020, reflecting the latest theoretical and empirical developments in AI and HR management. The findings reveal that a higher level of AI integration improves decision speed, reduces operational costs, and increases the accuracy of talent allocation. However, these efficiency gains are not independent of ethical considerations. Transparent algorithms are shown to significantly enhance employees’ trust and perceptions of fairness, whereas opaque systems tend to generate resistance and distrust. Furthermore, organizational culture plays a crucial moderating role. Companies with innovative and participatory cultures report better outcomes from AI implementation, while hierarchical cultures are associated with lower adoption success and ethical challenges. This research highlights the importance of aligning technical capabilities with social and cultural factors to optimize the use of AI in HR functions. The study contributes to the discourse on socio-technical systems by proposing an integrative framework that links AI integration, transparency, trust, and culture to key organizational outcomes. Practical implications include the need for transparent system design, ethical governance, and cultural readiness to support responsible AI adoption in HR.